Conceptual and applied models of enterprise sustainability: roadmap and indicative structure of process maturity - Fedorova , Yana; Ryzhakova , Galyna; Kushnir , Olesii; Herhi , Marian; Pereli , Diana; Wang , Yuitao (Ways to Improve Construction Efficiency, 2024)
The article presents the conceptual foundations for implementing process-oriented management as a key tool for modernizing developer enterprises in the construction sector. It is emphasized that under conditions of market dynamism, ecological challenges, and digital transformation, traditional management models are losing their effectiveness. The process-oriented approach enables formalization, optimization, and integration of business processes into a unified and controllable system. The study substantiates the relevance of adapting the Business Model for Sustainability (BMfS), which focuses on creating long-term value for all stakeholders, taking into account ESG criteria, circular economy principles, and digitalization. The application of the Model Management Case and Notation (MMCN) is analyzed, which allows the measurement of the "distance" between the current state of business processes and the target level of enterprise resilience. It is shown that MMCN facilitates the detection of deviations, scenario modeling, and adaptation to crisis conditions. Additionally, the study presents a five-level CMMI maturity scale adapted to the construction sector, which defines levels of process maturity — from chaotic to optimized. A practical development roadmap is proposed, which includes priorities, indicators, and tools aimed at enhancing organizational maturity in developer companies. Within the context of integration with other models (PMBOK, BSC, SCOR, BIM+Lean), the article justifies the synergistic potential of modern strategic management approaches in construction. It concludes that the combination of BMfS, MMCN, and CMMI forms a holistic paradigm of sustainable, digitally managed, and strategically adaptive development.